Mechanical Properties and Rapid Low-temperature Consolidation of Nanocrystalline Cu-ZrO2 Composites by Pulsed Current Activated Heating - Kang, Bo-Ram; Yoon, Jin-kook; Hong, Kyung-Tae; Shon, In-Jin (KOREAN INST METALS MATERIALS, 2015)
Metal-ceramic compositr can be obtained with an optimum combination of low density, high oxidation resistance, and high hardness of the ceramic and toughness of the metal. Therefore, metal matrix composites are recognized as candidates for aerospace, automotive, biomaterials, and defense applications. Despite its many attractive properties, the low fracture toughness of ZrO2 limits its wide application. One of the most obvious tactics to improve the mechanical properties has been to fabricate a nanostructured material and composite material. Nano-powders of Cu and ZrO2 were synthesized from 2CuO and Zr powders by high-energy ball milling. Nanocrystalline 2Cu-ZrO2 composite was consolidated within 5 minutes from mechanically synthesized powders of ZrO2 and 2Cu at low temperature, by a pulsed current activated sintering method. The relative density of the composite was 98.5%. The fracture toughness of 2Cu-ZrO2 composite in this study is higher than that of monolithic ZrO2, without great decrease of hardness.
Keywords: GROWTH; ENERGY; ZRO2